Predictive factors for complete pathologic response in luminal breast cancer: impact of ki67 and HER2 low expression - Isabel Miras; Ana Gil; Marta Benavent; María Ángeles Castilla; Begoña Vieites; María Ángeles Dominguez-Cejudo; Sonia Molina-Pinelo; Lina Alfaro; Javier Frutos; Manuel Ruiz-Borrego; Alejandro Falcón; Mónica Cejuela; et al. (Therapeutic Advances in Medical Oncology)
Background: Complete pathological response to neoadjuvant treatment (NAT) in breast cancer is associated with prolonged survival. Compared to other breast cancer immunophenotypes, luminal tumors are the least chemosensitive with low rates of pathological response within this molecular subtype. Thus, finding predictors of response in this subset remains challenging. The emerging concept of low human epidermal growth factor receptor 2 (HER2) expression has led to a repurpose of the current prognostic system. Little is known about its correlation with response to NAT. Objectives: This study aims to evaluate predictors of response in early-stage luminal breast cancer receiving neoadjuvant chemotherapy. Design: A total of 252 luminal patients who received NAT were retrospectively assessed in this cohort study. Methods: We analyzed the correlation of ki67 and HER2 low expression with the rate of pathologic response. Using ki67 as a continuous variable and applying the receiver operating characteristic curves method. Results: We identified that in patients with a ki67 expression level >37%, the probability of having a complete pathological response was 4.80 times higher (odds ratio = 4.80, 95% confidence interval: 1.92–12.04). In Her2-low breast cancer patients, Her2 expression did not correlate with a better response rate. Conclusion: In our study, a ki67 expression value greater than 37% constitutes a predictive biomarker of pathological complete response in the subgroup of patients with luminal B tumors and could be considered, therefore, an indicator for treatment decisions in this subgroup.